Impact analysis of hydraulic loading rate on constructed wetland: Insight into the response of bulk substrate and root-associated microbiota. (1st June 2022) - Zhang, Nan; Lu, Dingnan; Kan, Peiying; Yangyao, Jiannan; Yao, Zhiyuan; Zhu, David Z.; Gan, Huihui; Zhu, Baoyu
Highlights: Microbiota and nutrients removal are studied in pilot-scale CWs with two HLRs. HLR profoundly influences microbiota at the genus level and related removal efficiency. The co-occurrence network shows microbiota becomes more complex under higher HLR. A higher level of stochasticity is found in the microbiota under the higher HLR condition. Pathogens invasion is observed in the endosphere and proved to be affected by HLR. Abstract: Constructed wetland (CW) is an environment-friendly and low-cost technology for nutrients removal from domestic wastewater. For a well-tuned CW, hydraulic loading rate (HLR) is one of the critical factors, particularly under the challenging circumstance of more frequent heavy rainfall events brought by global warming. In this study, a comprehensive investigation was conducted to explore the influence of different HLRs on the CW's bulk substrate and root-associated microbiota aiming to yield new insight for CW management from a hybrid perspective of environmental microbiology and engineering science. The response of the microbial community and associated nutrients removal performance under different HLR settings were analyzed after a one-year operation. Results showed that the bulk substrate and rhizosphere genera involved in desulfurization and denitrification, such as Ferritrophicum, Sulfurimonas, and Sulfurisoma, were enriched in the higher HLR condition and associated with the higher total nitrogen (TN) and nitrate nitrogen (NO3 − -N) removal compared to the lower HLR condition. Co-occurrence network analysis demonstrated a more complex network under the higher HLR condition. Besides, it was observed that more stochastic in microbial assembly under the higher HLR condition. Surprisingly, zoonotic pathogens were observed and showed a greater prevalence under the higher HLR condition, indicating the potential correlation between HLR and pathogen intrusion. Collectively, this study revealed that the microbiota could be significantly altered under different HLR conditions, thereby resulting in differences in nutrients removal performance. Graphic abstract: Image, graphical abstract